Identification of miRNAs Affecting the Establishment of Brassica Alboglabra Seedling - Guo, Rongfang; Deng, Yanping; Huang, Zhongkai; Chen, Xiaodong; XuHan, Xu; Lai, Zhongxiong (Frontiers in Plant Science, 2016)
MicroRNAs (miRNAs) are important for plant development including seed formation, dormancy, and germination, as well as seedling establishment. The Brassica vegetable seedling establishment stage influences the development of high quality seedlings, but also affects the nutrient content of sprouts. Chinese kale (Brassica alboglabra) seedlings at different growth stages were used to construct two small-RNA (sRNA) libraries. We comprehensively analyzed the miRNAs in 2- and 9-day-old seedlings. An average of 11,722,490 clean reads were generated after removing low-quality reads and adapter contaminants. The results revealed that 37.65% and 26.69% of the sRNAs in 2- and 9-day-old seedlings, respectively, were 24 nt long. In total, 254 known mature miRNA sequences from 228 miRNA families and 343 novel miRNAs were identified. Of these miRNAs, 224 were differentially expressed between the two analyzed libraries. The most abundant miRNAs identified by sequence homology were miR156, miR167, and miR157, each with more than 100,000 sequenced reads. Compared with the expression levels in 2-day-old seedlings, MiR8154 and miR390 were the most up- and down-regulated miRNAs respectively in 9-day-old seedlings. Gene ontology enrichment analysis of the differentially expressed-miRNA target genes affecting biological processes revealed that most genes were in the “regulation of transcription” category. Additionally, the expression patterns of some miRNAs and target genes were validated by quantitative real-time polymerase chain reaction. We determined that development-associated miRNAs (e.g., bal-miR156/157/159/166/167/172/396), were highly-expressed during seedling-establishment stage, as were stress-related (bal-miR408) and metabolism-related (bal-miR826) miRNAs. Combined with the low level of targets SPL9 and AP2, it was concluded that miR156-SPL9 and miR172-AP modules play key roles during the B. alboglabra seedling establishment stage.